Android Application for Initial Screening of Atrial Fibrillation Using The Dempster Shafer Method - Oktaviono, Yudi Her; Yatijan, Marcella Aurelia; Purwanti, Endah; Rachmawati, Rizky Widya; Bustomi, M. Arief (Indonesian Applied Physics Letters, 2023)
Atrial Fibrillation (FA) is one of the most common types of heart rhythm abnormalities found in clinical practice in Indonesia. Atrial fibrillation can cause a stroke risk 5 times. Meanwhile, stroke cases themselves tend to rise and become one of the main causes of death every year. The cause of the high number of FA cases is the lack of public knowledge and awareness/sensitivity to the early symptoms of the disease. The purpose of this study was to design an android device for early screening of suspected FA through examination of pulse, complaints/symptoms and disease risk factors. The dempster shafer method is used as a decision making tool for suspected FA or not FA. The results of the detection system performance test, obtained a sensitivity of 93.5%, a specificity of 89.7%, and an accuracy of 91.7%. The test results of the android application design, namely Visual Design and User Interaction, Functionality, Stability and Performance and Overall Satisfaction, show a "good" response in all aspects.